Neuromuscular electrical stimulation for treating postpartum low back pain. Issue 28 (July 2018) - Li, Yue-peng; Cui, Xue; Liu, Shi-chen; Zhang, Shi-hua; Zhao, Yu-hang
Abstract : Abstract: In this retrospective study, we investigated the effect of neuromuscular electrical stimulation (NMES) in patients with postpartum low back pain (PPLBP). We included 67 patients with PPLBP in this study. All patients received NMES, each session 30 minutes, 1 session weekly for a total of 4 weeks. The primary outcome was measured by the reduction in pain intensity, based on the visual analogue scale (VAS). The secondary outcomes included functional status, measured by the Roland–Morris disability questionnaire (RMDQ), and quality of life, measured by the World Health Organization Quality of Life questionnaire (WHOQOL-BREF), as well as the adverse events related to the treatment. The outcome data were evaluated at baseline and at the end of 4-week treatment. After 4-week treatment, NMES did not exert better outcomes in pain relief, measured by VAS, and functional status, measured by RMDQ compared with those before the treatment. In addition, no significant improvement in quality of life, measured by WHOQOL-BREF, compared to it before the treatment. The results of our study did not find that NMES is effective in patients with PPLBP after 4-week treatment.